1890. Molecular Biology of SARS-CoV-2 and its Evolution within the Princeton University Campus Community. (15th December 2022) - Brewer, Jesse T; Yang, Qiqi; Aranovich, Irina; Wang, Wei; Notterman, Daniel; Daskalaki, Irini
Abstract: Background: SARS-CoV-2, a novel and highly pathogenic coronavirus, has caused unprecedented global disruption following its introduction into the human population. Beginning in January 2021, a NJ university invited all students to campus and initiated an asymptomatic testing protocol using weekly to twice-weekly PCR-based detection of human saliva samples. RNA extracted from PCR-positive human saliva samples was sequenced for surveillance purposes. Methods: Positive samples were submitted for RNA-Seq analysis (ARTIC amplicon sequencing protocol, Illumina MiSeq) and analyzed using Nextclade and USHER (comparison data from GISAID). Using sequencing data, the evolution, transmission, and emergence of SARS-CoV-2 variants were monitored over time in the campus community. Using sequencing data from NY, PA, and NJ in combination with University data, we performed an IQ-TREE based phylogenetic analysis. Results: Analyzing sequencing data of 1, 011 University positive samples we demonstrate that SARS-CoV-2 variants Delta (B.1.617.2) and Omicron (BA.1 and BA.2) were first to emerge following widespread vaccination and, quickly, became predominant. These trends witnessed on campus preceded those same variants emerging in New Jersey, providing evidence of local campus spread distinct from the state-wide pandemic. The analysis of 2, 359 total sequences from NY, PA, and NJ in combination with University data, provided evidence of the SARS-CoV-2 transmission chain on campus evolving from out-of-state (January 2021) to local (January 2022) spread over one year of the virus circulating within the community at large. Upon performing a Ct value analysis of 2, 822 Princeton University sequences, no significant differences were discovered between N gene Ct values when grouped by age or vaccination status. However, there were significant differences in Ct values between strains. The Emergence of SARS-CoV-2 Variants at Princeton University This plot represents the emergence of SARS-CoV-2 clades at Princeton University, organized by Nextstrain clade and displayed as a proportion out of one. Dates of sample collection range from January 25, 2021, to March 1, 2022. X-axis represents SARS-CoV-2 sample test date (grouped by month); Y-axis represents the count per day organized by Nextstrain clade. Conclusion: Sequencing of positive SARS-CoV-2 samples from population screening of a highly vaccinated University campus community allowed the detection of emergence of new variants that became predominant on campus irrespective of the circulation of variants in the surrounding area. Disclosures: All Authors : No reported disclosures.